Protective role of extracellular vesicles against oxidative DNA damage - Jordi Ribas-Maynou; Ana Parra; Pablo Martínez-Díaz; Camila Peres Rubio; Xiomara Lucas; Marc Yeste; Jordi Roca; Isabel Barranco (Biological Research)
Abstract Background Oxidative stress, a source of genotoxic damage, is often the underlying mechanism in many functional cell disorders. Extracellular vesicles (EVs) have been shown to be key regulators of cellular processes and may be involved in maintaining cellular redox balance. Herein, we aimed to develop a method to assess the effects of EVs on DNA oxidation using porcine seminal plasma extracellular vesicles (sEVs). Results The technique was set using a cell-free plasmid DNA to avoid the bias generated by the uptake of sEVs by sperm cells, employing increasing concentrations of hydrogen peroxide (H2O2) that generate DNA single-strand breaks (SSBs). Because SSBs contain a free 3’-OH end that allow the extension through quantitative PCR, such extension -and therefore the SYBR intensity- showed to be proportional to the amount of SSB. In the next stage, H2O2 was co-incubated with two size-differentiated subpopulations (small and large) of permeabilized and non-permeabilized sEVs to assess whether the intravesicular content (IC) or the surface of sEVs protects the DNA from oxidative damage. Results obtained showed that the surface of small sEVs reduced the incidence of DNA SSBs (P < 0.05), whereas that of large sEVs had no impact on the generation of SSBs (P > 0.05). The IC showed no protective effect against DNA oxidation (P > 0.05). Conclusions Our results suggest that the surface of small sEVs, including the peripheral corona layer, may exert a protective function against alterations that are originated by oxidative mechanisms. In addition, our in vitro study opens path to detect, localize and quantify the protective effects against oxidation of extracellular vesicles derived from different fluids, elucidating their function in physiopathological states.